Investigation the Digital Competence of Madrasah Teachers During the Covid-19 Pandemic - Supardi Supardi; Mohammad Viktor Farid Hakim (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this research was to investigate the digital competence of madrasah teachers during the covid-19 pandemic. The research used the qualitative method. It explored the phenomenon of madrasah teachers’ digital competence. The data were collected through observation and interviews. The study participants involved 1 principal and 9 teachers from grades 1 to 6. Data analysis consisted of data reduction, data presentation, conclusion drawing and triangulation. The study results conclude that the digital competence of madrasa teachers is still low, so that teaching and learning have not used multimedia technology. Therefore, the results of this study recommend the concept of training related to increasing the digital competence of madrasa teachers regularly because it had an important role in supporting the school's educational process.